2013
DOI: 10.1111/zph.12073
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Risks of Avian Influenza (H5) in Duck Farms in the Ayeyarwaddy Delta Region, Myanmar

Abstract: The following article from Zoonoses and Public Health, 'Risks of Avian Influenza (H5) in Duck Farms in the Ayeyarwaddy Delta Region, Myanmar' by H. H. Win, C. C. Su Mon, K. M. Aung, K. N. Oo, K. Sunn, T. Htun, T. Tiensin, M. Maclean, W. Kalpravidh and A. Amonsin published online on 09 August 2013 on Wiley Online Library (http://onlinelibrary.wiley. com/) has been retracted by the journal Editor-in-Chief, Mary Torrence, the Authors, and Blackwell Verlag GmbH, as the article has already been published in the Mya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This was followed by Japan (10; 14.9%), France (9; 13.4%), the United Kingdom (7; 10.4%) and other countries or categories including charities and multilateral organisations. Only a handful of papers reported funding from countries in the region: five papers acknowledged financial support from the Thai Research Council and/or Thai universities (Huynh et al, 2019; Lestari et al, 2019; Mon et al, 2012; Monteerarat et al, 2010; Win et al, 2014) and one paper benefitted from a scholarship by the Indonesia Endowment Fund for Education (Indrawan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by Japan (10; 14.9%), France (9; 13.4%), the United Kingdom (7; 10.4%) and other countries or categories including charities and multilateral organisations. Only a handful of papers reported funding from countries in the region: five papers acknowledged financial support from the Thai Research Council and/or Thai universities (Huynh et al, 2019; Lestari et al, 2019; Mon et al, 2012; Monteerarat et al, 2010; Win et al, 2014) and one paper benefitted from a scholarship by the Indonesia Endowment Fund for Education (Indrawan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These studies have demonstrated that domestic ducks are exposed to H5 avian influenza viruses and have the potential to play an important role as bridge species for avian influenza viruses between wild birds and terrestrial poultry. Serological evidence of Gs/GD/96-lineage H5Nx circulation in Ayeyarwady in 2009 was previously published [21]. A longitudinal study, conducted in 2009-2010, assessed the extent of transmission of H5 avian influenza viruses in duck flocks in Bago Region near a wetland/wild bird sanctuary [6].…”
Section: Introductionmentioning
confidence: 99%